Les transformations de la mobilisation sociale en Colombie : de l’émergence des alliances intersectorielles aux grèves nationales (2010-2021) - Julie Massal (Amnis)
The article offers a reflection on the major transformations of social mobilization in Colombia, while the negotiation and then the implementation of the Peace Agreement with the FARC guerrillas took place, during the 2010 decade. We are seeing the reorganization of traditional social actors (students and farmers) but above all the creation of cross-sector alliances between rural and urban actors. The major axes that articulate these alliances are examined and placed in the context of the fragile peace process, whose impasses or delays exacerbate socio-political expectations that have remained inaudible for a long time. The alliances allow an extension of mobilization strategies, which culminate in national strikes in 2019-2021. These favour the crystallization of the demand for the right to peaceful protest, coupled with the growing denunciation of repression, but also of deep socio-cultural and economic changes. The Colombian panorama of social mobilization has therefore truly been transformed, despite the persistence of rooted socio-political violence.